Exploring Cognitive, Personal, and Environmental Factors Influencing Sukuk Investment Intentions in Kandahar, Afghanistan: A Pre-Market Launch Study - Abdullah Ziarmal; Mohamad Yosaf Asak; Baryali Rohan; Mohammad Wase Sadiqi (El-Barka, 2026)
Sukuk, an Islamic financial instrument that has gained global recognition, remains a relatively new concept in Afghanistan. Recently, Afghanistan Islamic Bank, in collaboration with the Islamic Emirate of Afghanistan (IEA), plans to initiate Sukuk issuance in the near future. In this context, the present study examines investors’ perceptions and intentions regarding Sukuk investments in Kandahar, Afghanistan. This study employs a quantitative research design, collecting primary data from 300 investors in Kandahar, Afghanistan, using an adapted questionnaire. A cognitive social model comprising five independent constructs-awareness, compatibility, internal influence, external influence, and choice and preferences-was employed to examine the determinants of investment intention. The collected data were analyzed using SPSS software. The findings reveal that investors’ intentions are significantly influenced by awareness, compatibility, and social influence factors. From a practical perspective, the results provide valuable insights for Sukuk issuers and policymakers, highlighting the importance of cognitive, personal, and environmental factors in enhancing investors’ perceptions and intentions toward Sukuk investment.